INTELLECTUAL CAPITAL IMPACT ON TELECOMMUNICATION BUSINESS PERFORMANCE; IS IT REALLY MATTER? - Noel Singgih Haryo Pradono (Jurnal Ilmiah Ekonomi Bisnis, 2022)
This study aims to determine the effect of IC represented by Value Added Intellectual Capital (VAIC) on Telco business performance from inside and outside perspective. We use ROE to represent inside perspective and MVA per Share to represent outside perspective on business performance. The sample consist of Telco listed on Indonesia Stock Exchange and we used period of 2011 - 2018. This study conducts simple panel data regression statistic. The result showed that IC give significant impact on both on inside and outside business performance perspective.Keyword: Intellectual Capital, ROE, MVA Per Share